SEMANTIC FEATURES OF PROVERBIAL FORMATIONS IN ENGLISH, UZBEK AND KARAKALPAK LANGUAGES - Zhalgasov, N.M. (SCIENCE and SOCIETY, 2026)
This article deals with the study of the semantic features of English, Uzbek, and Karakalpak proverbs, revealing a number of similarities and differences among the analyzed languages. Positive, negative, and neutral evaluations of proverbial expressions in the studied languages are analyzed. The theoretical content of the article is supported by examples of proverbs from the compared languages.
Keywords: person; proverb; paremiological unit; pragmatics; national and cultural specificity; positive; negative; neutral evaluations